Deformations associated with arthrogryposis. Issue 9 (8th March 2021) - Hall, Judith G.
Abstract: Fetal movement is essential to normal human development. If the fetus does not move for whatever reason, then multiple organs and organ systems develop secondary and tertiary effects not normally present. Most of these are deformations with secondary structural damage.